Effects of the Droop Speed Governor and Automatic Generation Control AGC on Generator Load Sharing of Power System - Youssef Mobarak (International Journal of Applied Power Engineering (IJAPE), 2015)
In power system, as any inequality between production and consumption results in an instantaneous change in frequency from nominal, frequency should be always monitored and controlled. Traditionally, frequency regulation is provided by varying the power output of generators which have restricted ramp rates. The Automatic Generation Control AGC process performs the task of adjusting system generation to meet the load demand and of regulating the large system frequency changes. A result of the mismatches between system load and system generation, system frequency and the desired value of 50 Hz is the accumulation of time error. How equilibrium system frequency is calculated if load parameters are frequency dependent, and how can frequency be controlled. Also, how do parameters of a speed governor affect generated power. The transient processes before system frequency settles down to steady state. Finally, AGC in what way is it different from governor action. This paper presents new approaches for AGC of power system including two areas having one steam turbines and one hydro turbine tied together through power lines.